Analisis Rasio pada Kinerja Keuangan PT. Bakrieland Development Tbk - Lionel Justin; Matthew Tristan Afrianto; Marchellino Nathanael; Dyah Cahyasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the financial performance of PT Bakrieland Development Tbk. during the period 2020-2023 using the financial ratio approach. The main focus of this study is on the analysis of liquidity, solvency, profitability, and activity, by highlighting the use of cash flow statements as a tool to evaluate the company's financial condition. The results showed significant improvements in some aspects of the company's finances, such as an increase in the Quick Ratio, Net Profit Margin, and Return on Investment in recent years. However, some challenges are still found, especially in maintaining stable short-term liquidity and long-term debt management. In terms of solvency ratios, the company managed to reduce its dependence on debt, although fluctuations remained in the Debt to Equity Ratio. On the activity side, improved efficiency is reflected in the Fixed Asset Turnover and Inventory Turnover ratios, indicating better management of fixed assets and stock. This study highlights the importance of efficient cash flow management to maintain business continuity and competitiveness in the property sector. The findings provide strategic recommendations for companies to improve financial management and operational efficiency in the face of dynamic market challenges.